2008
DOI: 10.1111/j.1525-1446.2008.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture Brokerage Strategies in Diabetes Education

Abstract: The purpose of this article is to describe the elements of culture brokerage as applied in a recent educational pilot study among rural African Americans with type 2 diabetes mellitus. Culture Brokerage is a nursing intervention consisting of mediation between the traditional health beliefs and practices of a patient's culture and the health care system. The intervention of Culture Brokerage holds particular relevance for clinicians who work with chronically ill patients, including those with diabetes. Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…17(p1004) Furthermore, they explain that such narratives vary according to how strongly speakers feel about particular causes, their sources, and how integrated these causes seem to be across events. 17(p1008) Health care providers and diabetes educators in particular may find that features in the post-ED interview accounts identify opportunities to infuse cultural brokerage, 18 motivational interviewing, 19 and other potential interventions 20 that promote more effective selfmanagement.…”
Section: Methodsmentioning
confidence: 99%
“…17(p1004) Furthermore, they explain that such narratives vary according to how strongly speakers feel about particular causes, their sources, and how integrated these causes seem to be across events. 17(p1008) Health care providers and diabetes educators in particular may find that features in the post-ED interview accounts identify opportunities to infuse cultural brokerage, 18 motivational interviewing, 19 and other potential interventions 20 that promote more effective selfmanagement.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, individual and collective attitudes and motivations to engage in certain health behaviors are shaped by these cultural influences. Research indicates that diabetes interventions that are closely aligned with African American cultural values and beliefs have been successful in improving selfmanagement of the disease in this population (Betancourt, 2012; DeCoster & Cummings, 2005;Utz et al, 2008;Williams et al, 2006) For example, in a health education intervention study of rural African Americans with type 2 diabetes, Alexander et al (2008) utilized an anthropological strategy called “cultural brokerage.” This intervention was delivered by a nurse liaison who worked alongside participants to bridge divides between the health system, requirements for successful diabetes self-management, and cultural norms which influenced health behavior using what authors characterized as an “insider perspective.”…”
Section: Trends In Diabetes-related Psychosocial Care Of African Amermentioning
confidence: 99%
“…This perspective and the subsequent diabetes education intervention sessions were informed by focus groups of African Americans with diabetes which revealed that: participants preferred to make use of personal narratives and storytelling in the intervention curriculum; the acknowledgement and inclusion of family or significant others was decisive to effective diabetes management; there were barriers to self-care that were unique to the rural environment such as a lack of educational programs and medical specialists; there was a social stigma associated with being diagnosed with diabetes; and spirituality and faith was often utilized as a reference point and source of encouragement during challenges to managing illness (Alexander, Uz, Hinton, Williams, & Jones, 2008). This culturally-relevant knowledge became the guiding framework for how investigators tailored their recruitment methods, the content of intervention materials, the methods of delivering educational content, and the tone of interaction between study participants and their “nurse-broker” (Alexander et al, 2008).…”
Section: Trends In Diabetes-related Psychosocial Care Of African Amermentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found that the understanding of various diseases was based on cultural beliefs. For example, African Americans (Alexander et al ., 2008) and Appalachians (Tessaro et al ., 2005) tend to fear that diabetes will be a burden on their family and that diabetes is stigmatized because it is perceived as a self‐induced disease.…”
Section: Literature Reviewmentioning
confidence: 99%